Ontario Medical Association Position Paper on Health Effects of Ground-Level Ozone, Acid Aerosols and Particulate Matter. Issue 5 (3rd October 1998) - Boadway, BT; MacPhail, J; Jacobson, C
Abstract : This review of the evidence of the health effects of air pollutants focuses on research conducted in Ontario. Seven key Ontario studies are cited. These findings are highly significant for people living in the Great Lakes basin (and particularly the Windsor-Quebec corridor), where high levels of certain air pollutants (eg, ground-level ozone and ultra-fine particles) occur more frequently than in other parts of Canada. The issue is a serious one, requiring an integrated and comprehensive approach by many stakeholders, including the active involvement of organized medicine. It is important that the health effects of these air pollutants are understood. Governments must act to reduce emission levels through statue and regulation bolstered by noncompliance penalties. The findings of research have included the following: in a Toronto study, a 2% to 4% excess of respiratory deaths were attributable to pollutant levels; children living in rural Ontario communities with the highest levels of airborne acids were significantly more likely to report at least one episode of bronchitis, as well as to show decreases in lung function; and have been linked to increases in pollutants, emergency room visits and hospitalizations in Ontario. Every Ontarian is affected by air pollutants, although he or she may be unaware of the asymptomatic effects such as lung and bronchial inflammation. This health problem is preventable; while physicians know of the adverse health impacts of air pollution and they are concerned, individually they now focus on the treatment of symptoms. The major recommendations of the report are as follows: * Enactment of more stringent sulphur and nitrogen oxide emission limits, including a provincewide sulphur dioxide reduction of 75% from current cap levels, and the maximum allowable nitrogen oxides emission limits of 6000 tonnes annually from Ontario Hydro. * New transportation sector emission limits that should include California-level standards for light and heavy duty vehicles, reductions from off-road engines, an expanded vehicle inspection and maintenance program, and tougher standards for sulphur-in-fuel content. * Petitioning the United States Environmental Protection Agency administrator under Section 115 of the United States Clear Air Act to require reductions in the American emission of sulphur dioxide and nitrogen oxides, which damage the health of Canadian residents and their environment. * Physician advice to patients about the risks of smog exposure, physician support for more health effects research on air pollution, and physician promotion of the development of air pollution-related health education materials. The recommendations discussed in this paper will, if acted upon, lead to a significant reduction in the overall burden of illness from air pollutants, especially in children and the elderly. These recommendations have been selected from a review of recommendations made by various authorities, and are those that the OMA feels a particular responsibility to support.